Cardio-Metabolic Indices and Metabolic Syndrome as Predictors of Clinical Severity of Gastroenteropancreatic Neuroendocrine Tumors - Barrea, Luigi; Muscogiuri, Giovanna; Modica, Roberta; Altieri, Barbara; Pugliese, Gabriella; Minotta, Roberto; Faggiano, Antongiulio; Colao, Annamaria; Savastano, Silvia (Frontiers in Endocrinology, 2021)
Background: Obesity, mainly visceral obesity, and metabolic syndrome (MetS) are major risk factors for the development of type 2 diabetes, cardiovascular diseases, and cancer. Data analyzing the association of obesity and MetS with gastroenteropancreatic neuroendocrine neoplasms (GEP-NEN) are lacking. Fatty liver index (FLI) is a non-invasive tool for identifying individuals with non-alcoholic fatty liver disease (NAFLD). Visceral adiposity index (VAI) has been suggested as a gender-specific indicator of adipose dysfunction. Both indexes have been proposed as early predictors of MetS. This study aimed to investigate the association of FLI VAI as early predictors of MetS with gastroenteropancreatic neuroendocrine tumors (GEP-NET). Methods: A cross-sectional, case-control, observational study was carried out at the ENETS Centers of Excellence Multidisciplinary Group for Neuroendocrine Tumors, University “Federico II”. VAI and FLI were calculated. Results: We enrolled 109 patients with histologically confirmed G1/G2 GEP-NET (53 M; 57.06±15.96 years), as well as 109 healthy subjects, age, sex- and body mass index-matched. Forty-four GEP-NET patients were G2, of which 21 with progressive disease, and 27 patients had metastases. GEP-NET patients had a higher value of VAI (p<0.001) and FLI (p=0.049) and higher MetS presence (p<0.001) compared with controls. VAI and FLI values, and MetS presence were higher in G2 than in G1 patients (p<0.001), in patients in progressive disease, and in metastatic vs non-metastatic patients (p<0.001). In addition, higher values of VAI and FLI and higher MetS presence were significantly correlated with the worst clinical severity of NENs. The cut-off values for the FLI and MetS to predict high grading of GEP-NETs and the presence of metastasis were also provided. Conclusions: This is the first study investigating an association between VAI and FLI as early predictors of MetS and GEP-NET. Our findings report that the worsening of clinicopathological characteristics in GEP-NET is associated with higher presence of MetS, NAFLD, evaluated by FLI, and visceral adiposity dysfunction, evaluated by VAI. Addressing the clinical evaluation of MetS presence, NAFLD, and visceral adiposity dysfunction might be of crucial relevance to establish targeted preventive and treatment interventions of NEN-related metabolic comorbidities.